The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2169/internalmedicine.53.2114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Treatment Outcomes of Nineteen Japanese Patients with Gastrointestinal Bezoars

Abstract: Objective To analyze the clinical characteristics of patients with gastrointestinal bezoars and their response to therapy. Patients We retrospectively reviewed the cases of 19 patients diagnosed with gastrointestinal bezoars at the Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences or one of 15 collaborating institutions between December 2004 and August 2013. We investigated the epidemiology and etiology of the gastrointestinal bezoars by determining the gender, age at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 26 publications
(34 reference statements)
3
59
0
3
Order By: Relevance
“…The immersion experiment revealed that Coca-Cola did not permeate the bezoar even after immersion for 120 hours. Our study results are consistent with those previously reported that indicated that Coca-Cola is ineffective for dissolving persimmon phytobezoars (6,8,(15)(16)(17). In our previous study, we investigated the ultrastructure of a persimmon bezoar by scanning electron microscopy and found that a high-density layer 20-to 50-μm thick constituted the exterior of the phytobezoar (18).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The immersion experiment revealed that Coca-Cola did not permeate the bezoar even after immersion for 120 hours. Our study results are consistent with those previously reported that indicated that Coca-Cola is ineffective for dissolving persimmon phytobezoars (6,8,(15)(16)(17). In our previous study, we investigated the ultrastructure of a persimmon bezoar by scanning electron microscopy and found that a high-density layer 20-to 50-μm thick constituted the exterior of the phytobezoar (18).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, reports from Korea indicated that 3 L of cola lavage or drinking resulted in complete dissolution of non-persimmon phytobezoars in 66.7% (four of six) of cases, while it was not at all effective in patients with persimmon phytobezoars (0 of 11 cases) (8). Our previous case series also showed that persimmon phytobezoars were not dissolved by Coca-Cola beverages alone and they required endoscopic or surgical removal (6). Such clinical results indicate that persimmon phytobezoars are resistant to cola beverages due to their structural rigidity, which prevents permeation of liquid.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, multiple cases of persimmon phytobezoar (diospyrobezoar) have been reported in regions where the residents frequently consume fresh persimmon fruits and dried persimmons. 10 Our results of higher prevalence of trichobezoars in young females with trichotillomania and trichophagia were resembling other previous reports which show that trichobezoars are nearly always gastric and diagnosed in young females. 11 The clinical presentation of bezoars in our study was not different from other studies, except for the case of sigmoid colon bezoar caused by a very rare type of foreign body bezoar that presented with sigmoid volvolus and acute abdomen.…”
Section: Discussionsupporting
confidence: 90%
“…While all the attempts failed in one study, it was successful in many others. 10,12,14 Laparoscopic removal of bezoars continues to be controversial. 12 The first described case of laparoscopic removal of a gastric trichobezoar was in 1998 and since then a few case reports described successful laparoscopic removal of gastric bezoars, generally in adults and adolescents.…”
Section: Discussionmentioning
confidence: 99%